The effect of biostimulant applicationt on vegetatif growth of delayed transplant melon seedlings - Audia, Fitri; Rahayu, Wiwik Endah; Romalasari, Atika; Jaenudin, Nasywa Mutiara (Universitas Muhammadiyah Mataram, 2025)
Melon (Cucumis melo L.) is a high-economic-value horticultural commodity whose production success greatly depends on optimal early vegetative growth. Melon seedlings transplanted late are prone to physiological stress that can hinder vegetative development, requiring strategies to support plant adaptation. This study serves as a preliminary research to assess the effectiveness of the recommended dosage of 1% on the vegetative growth of delayed transplanted melon seedlings (16 days after sowing). The experiment was conducted with two treatments: no biostimulant application as control (P0) and 1% biostimulant application (P1), each with 16 replications, resulting in a total of 32 experimental units. Observed parameters included plant height, leaf number, stem diameter, and internode length at 7, 14, and 21 days after transplanting (DAT). The t-test results showed that biostimulant application had no significant effect (p<0.05) on all observed variables through the end of the vegetative phase. This study indicates that applying biostimulant at a 1% concentration was ineffective in restoring vegetative growth in delayed-transplant melon seedlings, suggesting the need for further research with different doses and application frequencies.